DELAYED SUPRAMALLEOLAR FLAP - AN INNOVATIVE TECHNIQUE FOR ENHANCED VIABILITY - Ahmed, Syed Kamran; Hashmi, Pervaiz Mehmood (Journal of Ayub Medical College Abbottabad, 2005)
Background: Delaying flap rotation for 48 to 72 hours leads to opening of choke anastomotic vessels linking adjacent vascular territories. This mechanism enhances flap circulation. Lateral supramalleolar flap with larger dimensions or vascular variations can potentially have survival problems. The purpose of this study is to assess the outcome of delayed lateral supramalleolar flap. Methods: This descriptive case series was conducted at Aga Khan University Hospital, Karachi from May 1999 to December 2004. Eight cases of delayed lateral supramalleolar flap were identified through medical records maintained through Health Information Management Systems (HIMS). A detailed questionnaire was developed addressing variables of interest. Results: Eight patients required flap delay for 48 hours out of 25 patients, who underwent lateral supramalleolar flap for coverage of foot and ankle soft tissue defects. There were six male (75%) and two female (25%) patients with average age of 31.25 years ranging from 5-52. The reasons for delaying lateral supramalleolar flap were larger flap dimension in four (50%), absent peroneal artery perforator in three (37.5%) and one patient (12.5%) had poor circulation in immediate postoperative period. All the patients required two stage procedure and had excellent coverage of defects. No flap failure occurred subsequent to the delay procedure. Conclusions: Flap delay enhanced survival and extended the viable dimensions of lateral supramalleolar flap. Compromised circulation in larger flaps and flaps with vascular variations can be improved by delaying flap transfer to the recipient site for 48 hours following its elevation. Keywords: Delayed flap, Lateral supramalleolar flap, Foot and ankle soft tissue defects.